Endoscopic Versus Open Cubital Tunnel Release: A Systematic Review and Meta-Analysis. (March 2016) - Aldekhayel, Salah; Govshievich, Alexander; Lee, James; Tahiri, Youssef; Luc, Mario
Background: Several surgical techniques exist for treatment of cubital tunnel syndrome. Endoscopic cubital tunnel release (ECTuR) has been recently reported as a promising minimally invasive technique. This study aims to compare outcomes and complications of open cubital tunnel release (OCTuR) and ECTuR in the treatment of idiopathic cubital tunnel syndrome.Methods: A systematic review of the literature (1980-2014) identified 118 citations. Studies including adults with idiopathic cubital tunnel treated exclusively by ECTuR or OCTuR were included. Outcomes of interest were postoperative grading, complications, number of reoperations, and the need for intraoperative conversion to another technique. Postoperative outcomes were combined into a uniform scale with 4 categories: "excellent, " "good, " "fair, " and "poor."Results: Twenty studies met the inclusion criteria (17 observational and 3 comparative), representing 425 open and 556 endoscopic decompressions. In the open group, 79.8% experienced "good" or "excellent" results with 12% complication rate and 2.8% reoperation rate. In the endoscopic group, 81.8% experienced "good" or "excellent" results with 9% complication rate and 1.6% reoperation rate. Meta-analysis of 3 comparative studies demonstrated a significantly lower overall complication rate with ECTuR. Subgroup analysis of complications revealed a significantly higher incidence of scar tenderness and elbow pain with OCTuR.Conclusions: The current study demonstrates similar effectiveness between the endoscopic (ECTuR) and open (OCTuR) techniques for treatment of idiopathic cubital tunnel syndrome with similar outcomes, complication profiles, and reoperation rates.